A bibliometric analysis of the theme trends and knowledge structures of pulmonary embolism from 2017 to 2021 - Fan, Jingjing; Xu, Xiaoman; Zhao, Li (Frontiers in Medicine, 2023)
Background: Pulmonary embolism (PE) has been a popular area of research among respiratory physicians. According to PubMed literature, the distribution pattern and knowledge structures of PE were sorted out. Methods: The literature on PE from January 1, 2017, to December 30, 2021, was retrieved from the PubMed database. Biclustering analysis, co-word analysis, strategy diagram analysis, and social network analysis were then carried out to identify immature or recently emerging research hotspots for researchers. Results: Out of all the retrieved MeSH terms and subheadings, 52 MeSH terms/MeSH subheadings with a high frequency were found, and hot subjects were sorted into 6 clusters. In the strategy diagram, the epidemiology, etiology, and drug therapy of PE were the central topics for continued development. Diagnostic imaging, complications, and diagnosis of PE were the unexplored topics. Social network analysis showed that topics at the periphery, such as surgical treatment of pulmonary hypertension, prevention and control of postoperative complications, and metabolism and analysis of fibrin/fibrinogen degradation products were considered new research hotspots with considerable research space. Conclusions: The findings from the analysis of PE-related research hotspots may aid in providing researchers with suggestions for starting new studies as well as a complete overview of the state of the field now.